Effects of a benzalkonium chloride surfactant-sodium hypochlorite combination on microhardness and mineral content of dentin = Efectos de una combinación de tensioactivo de cloruro de benzalconio e hipoclorito de sodio en la microdureza y el contenido mineral de la dentina - Ezgi Aslantas, Eda; Aksel, Hacer; Dogan Buzoglu, Hatice (2024)
This study aimed to investigate the impact of the combination of Benzalkonium chloride (BAC) and sodium hypochloride (NaOCl) and its application after ethylenediaminetetraacetic acid (EDTA) in root canal irrigation procedures on the microhardness and mineral content of dentin. Distal roots of mandibular third molars were embedded in auto-polymerizing acrylic resin, sectioned coronally to apically resulting in fifty-four root sections. Thirty sections underwent microhardness evaluation, and twenty-four sections were randomly chosen for mineral analysis. The microhardness assessment comprised three groups: Group 1 (2.5% NaOCl), Group 2 (2.5% NaOCl with 0.084% BAC), and Group 3 (2.5% NaOCl with 0.084 BAC post-17% EDTA). Initial and post-irrigation microhardness values were measured for each group. For mineral analysis, samples were categorized into four groups: distilled water, 2.5% NaOCl, 2.5% NaOCl with 0.084% BAC, and 17% EDTA+2.5% NaOCl with 0.084% BAC. X-ray photoelectron spectroscopy immediately measured magnesium, phosphorus, and calcium mineral contents on dentin surfaces post-irrigation. Results indicated a significant reduction in root dentin microhardness for all solutions (p<0.05). However, no statistically significant difference in the percentage of reduction was observed among the groups (p>0.05). XPS analysis revealed no significant disparity in dentin surface mineral content among the groups (p>0.05). In conclusion, the addition of Benzalkonium chloride to sodium hypochloride, either alone or after EDTA, did not induce a significant alteration in dentin microhardness or mineral content. These findings contribute to a nuanced understanding of dental irrigation protocols and their effects on dentin properties during endodontic procedures.
Este estudio tuvo como objetivo investigar el impacto de la combinación de cloruro de benzalconio (BAC) e hipocloruro de sodio (NaOCl) y su aplicación después del ácido etilendiaminotetraacético (EDTA) en procedimientos de irrigación del conducto radicular sobre la microdureza y el contenido mineral de la dentina. Las raíces distales de los terceros molares mandibulares se incluyeron en resina acrílica autopolimerizable y se seccionaron de coronal a apical, lo que dió como resultado cincuenta y cuatro secciones de raíz. Treinta secciones se sometieron a una evaluación de microdureza y veinticuatro secciones fueron elegidas al azar para el análisis mineral. La evaluación de la microdureza comprendió tres grupos: Grupo 1 (2,5% NaOCl), Grupo 2 (2,5% NaOCl con 0,084% BAC) y Grupo 3 (2,5% NaOCl con 0,084 BAC post-17% EDTA). Para cada grupo se midieron los valores de microdureza inicial y post-irrigación. Para el análisis mineral, las muestras se clasificaron en cuatro grupos: agua destilada, 2,5% NaOCl, 2,5% NaOCl con 0,084% BAC y 17% EDTA+2,5% NaOCl con 0,084% BAC. La espectroscopía fotoelectrónica de rayos X midió inmediatamente el contenido de minerales de magnesio, fósforo y calcio en las superficies de la dentina después de la irrigación. Los resultados indicaron una reducción significativa en la microdureza de la dentina radicular para todas las soluciones (p<0,05). Sin embargo, no se observó diferencia estadísticamente significativa en el porcentaje de reducción entre los grupos (p>0,05). El análisis XPS no reveló ninguna disparidad significativa en el contenido mineral de la superficie de la dentina entre los grupos (p>0,05). En conclusión, la adición de cloruro de benzalconio al hipocloruro de sodio, solo o después de EDTA, no indujo una alteración significativa en la microdureza o el contenido mineral de la dentina. Estos hallazgos contribuyen a una comprensión matizada de los protocolos de irrigación dental...
En revista Odóvtos, vol. 26, no.2 (mayo-agosto 2024)
Descripción basada en el contenido visto el 04 de febrero, 2025
También disponible en formato HTML y EPUB